Heat transfer analysis on ferromagnetic hybrid nanofluid dynamics with the effect of thermal radiation and induced magnetic field - Krishnaveni, T. Radha; Srinivasa Kumar, B.; Reddy, G.V. Ramana (Journal of Naval Architecture and Marine Engineering, 2026)
By clarifying the impact of thermal radiation and induced magnetisms, this study explains the heat transformation analysis on ferromagnetic hybrid nano fluid dynamics. When heat transfer occurs in the presence of generated heat within the boundary layer, the induced magnetic field is taken into account. Heat generation and fluid thermal analysis are thought to be important within the boundary layer (BL) in order to standardize the dynamics process. PDEs, or partial differential equations, are used to describe the model. Ordinary differential equations (ODEs) are a further transformation of PDEs. The set of ODEs has been investigated using the spectrum relaxation method (SRM). The SRM is an iterative method for solving differential equations that makes use of the Gauss-seidel technique notion. It is observed that a higher Prandtl number causes the velocity and temperature to decrease. The thickness of the momentum BL is significantly influenced by the induced magnetic field. Together with thermal BL thickness, it was found that heat generation and thermal radiation increased momentum. Applications of this research can be found in the automotive and thermal engineering sectors. It is observed that the new analysis concurs with earlier publications. Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 119-127